BERITA MODERASI BERAGAMA REPUBLIKA ONLINE: PERSPEKTIF FRAMING ROBERT N. ENTMAN - Sunaryanto Sunaryanto; Ahmad Rofi Syamsuri; zulkifli zulkifli (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2022)
This study aims to interpret the news of religious moderation in Republika Online. The research data used is from the documentation of religious moderation news in Republika Online. The theory used is the framing of Robert N. Entman. The conclusion of the study is that the news of religious moderation in the Republika Online media is a text that has multiple interpretations. Overall, the framing built by the Republic of Indonesia Online is moderate and in line with moderate by developing tolerance and building nationalism. In the end, news of religious moderation in the Republika Online media is a text that has multiple interpretations. The news can be interpreted in different ways according to the different ideological contexts by each newsreader. Like the constructionist school of thought, there is no right or wrong in interpreting news texts, because news texts are subjective constructions of reality. Although subjective, Republika Online tries to build news framing more on nationalism. In the news of religious moderation related to Muslims, Republika Online develops a framing that does not only defend Muslims. As a national media, Republika Online tries to develop a framing that can be accepted by the wider community, both Muslim and non-Muslim communities.